2022
DOI: 10.3390/bios12080584
|View full text |Cite
|
Sign up to set email alerts
|

Total Internal Reflection Ellipsometry Approach for Bloch Surface Waves Biosensing Applications

Abstract: A one-dimensional photonic crystal with an additional TiO2 layer, supporting Bloch surface waves (BSW), was used for enhanced signal sensitivity for the detection of protein interaction. To compare the optical response of BSW and photonic crystals (PC), bovine serum albumin and specific antibodies against bovine serum were used as a model system. The results obtained show the enhanced sensitivity of p- and s- BSW components for the 1D PC sample with an additional TiO2 layer. Furthermore, a higher sensitivity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…They also demonstrated that the morphological and optical properties could be tuned by the deposition conditions without any pre- or post-treatment. Additionally, these structures supporting surface waves such as Bloch surface waves (BSW) could be used for advanced biosensing applications with enhanced sensitivity for protein interaction detection [ 82 ]. Multilayered structures have been used not only to tune the plasmon resonance but also to increase the number of hotspots [ 83 , 84 ].…”
Section: Designing Substrates and Chips For Biosensing Applicationsmentioning
confidence: 99%
“…They also demonstrated that the morphological and optical properties could be tuned by the deposition conditions without any pre- or post-treatment. Additionally, these structures supporting surface waves such as Bloch surface waves (BSW) could be used for advanced biosensing applications with enhanced sensitivity for protein interaction detection [ 82 ]. Multilayered structures have been used not only to tune the plasmon resonance but also to increase the number of hotspots [ 83 , 84 ].…”
Section: Designing Substrates and Chips For Biosensing Applicationsmentioning
confidence: 99%
“…The optical dispersion of these surface waves are below the light cone which is similar to the SPP. Thus, BSW share some of the optical features [ 15 ] as the SPP, and therefore they are used widely for optical biosensing in TIR configuration as SPR biosensors [ 16 , 17 ]. It has been shown that spectral sensitivity of the BSW biosensors is lower than SPR; however, due to lower losses in periodic dielectric structures the angular sensitivity of reflected polarized intensity or ellipsometric parameters was better than for SPR [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The physical principles of such optical sensors are based on the exploitation of the evanescent field as a sensing probe. Various types of optical sensors for chemical or biological detection employs silicon photonics such as those based on photonic crystals [ 24 , 25 ], whispering gallery modes [ 26 ], Bloch surface waves [ 27 ], Mach–Zender interferometers [ 28 ], photoluminescence [ 29 ], and many others. Other widely used sensing surfaces are metallic; commonly, the surfaces are gold or silver, but other metals such as titanium or aluminum are also used [ 30 ].…”
mentioning
confidence: 99%